Heinz Dome, New York World's Fair (Curt Teich & Co.)
The beauty of the night lighting during the New York World's Fair is suggested in this striking photograph taken during a night test. It shows the trees, illuminated by hidden capillary mercury tubes, and the 90-foot high Heinz dome, bathed in indirect fluorescent tube lighting - all reflected in a pool in Constitution Mall. Buildings at the Fair take on brightness and color from these new sources of light, as a climax to the Cosmic Ray opening night spectacle at the Trylon and Persiphere.